Case report: isolated glans penis gangrene - Syazwan, Abu; Lee, Chin Yiun; Mohamed, S. O.; Salauddin, Syahril Anuar; Ab. Rashid, Islah Munjih; Kamarulzaman, Mohd Nazli; Ghazali, Hamid (Wiley, 2017)
Introduction